Histologic chorioamnionitis does not modulate the oxidative stress and antioxidant status in pregnancies complicated by spontaneous preterm delivery - Martin, Laura Fernandes [UNESP]; Moço, Natália Prearo [UNESP]; de Lima, Moisés Diôgo; Polettini, Jossimara; Miot, Hélio Amante [UNESP]; Corrêa, Camila Renata [UNESP]; Menon, Ramkumar; da Silva, Márcia Guimarães [UNESP] (Springer Nature, 2017)
Background: Infection induced-inflammation and other risk factors for spontaneous preterm birth (PTB) and preterm premature rupture of membranes (pPROM) may cause a redox imbalance, increasing the release of free radicals and consuming antioxidant defenses. Oxidative stress, in turn, can initiate intracellular signaling cascades that increase the production of pro-inflammatory mediators. The objective of this study was to evaluate the oxidative damage to proteins and antioxidant capacity profiles in amniochorion membranes from preterm birth (PTB) and preterm premature rupture of membranes (pPROM) and to determine the role of histologic chorioamnionitis in this scenario. Methods: We included 27 pregnant women with PTB, 27 pPROM and 30 at term. Protein oxidative damage was assayed by 3-nitrotyrosine (3-NT) and carbonyl levels, using enzyme-linked immunosorbent assay (ELISA) and modified dinitrophenylhydrazine assay (DNPH), respectively. Total antioxidant capacity (TAC) was measured by ELISA. Results: Protein oxidative damage determined by carbonyl levels was lower in PTB group than pPROM and term groups (p < 0.001). PTB group presented higher TAC compared with pPROM and term groups (p = 0.002). Histologic chorioamnionitis did not change either protein oxidative damage or TAC regardless of gestational outcome. Conclusion: These results corroborates previous reports that pPROM and term birth exhibit similarities in oxidative stress- induced senescence and histologic chorioamnionitis does not modulate oxidative stress or antioxidant status.
Keywords: Antioxidant capacity; Histologic chorioamnionitis; Oxidative stress; Preterm birth